1989
DOI: 10.1073/pnas.86.23.9606
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid requirements for recovery of sensitivity after visual-pigment bleaching in isolated photoreceptors.

Abstract: After visual-pigment bleaching, single isolated rod photoreceptors of Ambystoma tigrinum recover their sensitivity to light when supplied with 11-cis-retinal from liposomes or with li-cis-retinal bound to interphotoreceptor retinoid-binding protein. Bleached rods do not recover sensitivity, or do so only very slowly, after exposure to 11-cis-retinol. The latter retinoid is "toxic" in that rods actually lose sensitivity in its presence. In contrast, bleached isolated cone cells recover sensitivity when either r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
155
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(164 citation statements)
references
References 33 publications
9
155
0
Order By: Relevance
“…Cones, but not rods, can use 11-cis-ROL as a chromophore precursor to regenerate bleached opsin pigments (10,12,13). The isomerase in the noncanonical pathway is dihydroceramide desaturase (DES1) (11).…”
mentioning
confidence: 99%
“…Cones, but not rods, can use 11-cis-ROL as a chromophore precursor to regenerate bleached opsin pigments (10,12,13). The isomerase in the noncanonical pathway is dihydroceramide desaturase (DES1) (11).…”
mentioning
confidence: 99%
“…Moreover, it had been shown in the 1980s that in the retina of the cone-dominant chicken the major source of retinylesters are 11-cis REs localized inside the neural retina, whereas rod-dominant species, such as frogs and cows show a pre-dominance of all-trans REs in the RPE (Bridges and Alvarez, 1987;Rodriguez and Tsin, 1989). Bleached salamander rod outer segments are only capable of recovering their visual sensitivity upon administration of exogenous 11-cis RAL, but not ROL, whereas cones were able to utilize both retinoid sources (Jones et al, 1989).…”
Section: Alternative Cone Visual Cycle In Cone-dominant Speciesmentioning
confidence: 99%
“…Knocking-down either cralbp paralog did not result in complete absence of 11-cis RAL, as cone photoreceptors are capable of utilizing the 2 nd source of recycled visual pigment (from the RPE or Müller cells). It has been shown that cone photoreceptors possess a 11-cis ROL dehydrogenase activity, capable of oxidizing 11-cis ROL into 11-cis RAL (Jones et al, 1989;Mata et al, 2002), and are able to regenerate visual pigment from 11-cis ROL or 11-cis RAL (Jones et al, 1989).…”
Section: Interestingly Schonthaler Et Al Had Similarly Not Observedmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cone-dominant retina, the oxidation of 11-cis-ROL to 11-cis-RAL is NADP dependent and takes places in cones (Mata et al 2002), whereas in rod-dominant eyes, this oxidation reaction is NAD dependent. In an early study using isolated rods and cones from salamander, it was shown that 11-cis-ROL added to the medium could confer light sensitivity to photobleached cones, but not to rods ( Jones et al 1989), suggesting that cones contain RDH(s) that catalyses oxidation of 11-cis-ROL to 11-cis-RAL. Haeseleer et al (2002) showed that RDH12 expressed in the photoreceptors could be involved in the production of 11-cis-RAL from 11-cis-ROL during regeneration of the cone visual pigments.…”
Section: Diversity Of the Visual Retinoid Cycle In Vertebrates (A) Romentioning
confidence: 99%